The Segond fracture occurs at the site of lowest sub‐entheseal trabecular bone volume fraction on the tibial plateau. Issue 6 (8th August 2020) - Mullins, William; Jarvis, Gavin E.; Oluboyede, Daniel; Skingle, Linda; Poole, Ken; Turmezei, Tom; Brassett, Cecilia
Abstract: In a series of human cadaveric experiments, Dr. Paul Segond first described the avulsion injury occurring at the anterolateral tibial plateau that later took his name. The fracture is thought to arise as a consequence of excessive tibia internal rotation which often also elicits damage to other connective tissue of the knee. The exact mechanism behind the avulsion is, however, unclear. A number of ligamentous structures have been proposed in separate studies to insert into the Segond fragment. Suggestions include the iliotibial band (ITB), biceps femoris and the controversial 'anterolateral ligament' (ALL). Despite increasing knowledge of tibial plateau bony microarchitecture in both healthy and disease states, no studies have yet, to our knowledge, considered the role of tibial sub‐entheseal bone structure in pathogenesis of the Segond fracture. The goal of this study was thus to elucidate the differences in trabecular properties at regions across the tibial plateau in order to provide an explanation for the susceptibility of the anterolateral region to avulsion injury. Twenty human tibial plateaus from cadaveric donors were dissected and imaged using a Nikon‐XTH225‐μCT scanner with <80 μm isotropic voxel size. Scans were reconstructed using MicroView 3D Image Viewer and Analysis Tool. Subsequent virtual biopsy at ten anatomically defined regions of interest (ROI) generated estimates of bone volume fraction ('bone volume divided by total volume' (BV/TV)). The overall mean BV/TV value across all 20 tibiae and all 10 ROIs was 0.271. Univariate repeated‐measurements ANOVA demonstrated that BV/TV values differed between ROIs. BV/TV values at the Segond site (Sα, Sβ or Sγ) were lower than all other ROIs at 0.195, 0.192 and 0.193, respectively. This suggests that, notwithstanding inter‐ and intra‐specimen variation, the Segond site tends to have a lower trabecular bone volume fraction than entheseal sites elsewhere on the tibia. Since BV/TV correlates with tensile and torsional strength, the lower BV/TV at the Segond site could equate to a region of local weakness in certain individuals which predisposes them to an avulsion injury following the application of force from excessive internal rotation. The low BV/TV recorded at the Segond site also challenges the idea that the fracture occurs due to pull from a discrete 'anterolateral ligament', as the tension exerted focally would be expected to elicit a hypertrophic response in line with Frost's Mechanostat hypothesis. Our data would instead agree with the aforementioned reports of the fibrous band at the Segond site being part of a broader insertion of an 'anterolateral complex'. Abstract : MicroCT data from cadaveric tibiae demonstrates that trabecular bone volume fraction at the site of the Segond fracture is significantly lower than other entheseal sites across the tibial plateau. This may equate to a region of local weakness which can predispose certain individuals to the avulsion injury following the application of excessive tibial internal rotation.